Socio-psychological predictors of academic achievement - Penano, Leticia Cecilia Zabala 1947- (s.n.], 1973)
Certain socio-psychological causes of underachievement in the University of the Philippines High School (U.P.High School) were determined in this study. It sought to find out the interaction among the following variables in conjunction with academic underachievement: (1) the student's need for achievement; (2) the student's need for affiliation; and (3) the values of the peer society the student belongs to.